New technologies adoption and diffusion patterns in developing countries - An empirical study for the period 2000-2011 - Ewa Lechman (Gdańsk University of Technology, Faculty of Management and Economics, 2013)
In recent years, enormous changes are noted worldwide when broad adoption of new Information and Communication Technologies (ICTs). These unique technologies – often perceived as economic development incentives – have a great ability to spread at high pace and low cost in world countries, bringing to people opportunities to contribute to economic development and growth. New Technologies play a special role in developing countries, where their in-country adoption lies in the centre of development strategies. ICTs are treated as tools which bring to people access to information, education and knowledge, offering unlimited possibilities for wealth-creation. The paper, purely empirical in nature, reports on the pace of adoption of new Information and Communication Technologies in developing countries, and – additionally – investigates country-specific ICTs diffusion patterns. We expect to uncover the S-shape curve in the diffusion process in most of developing countries, as well as in the whole country sample. For the analysis purposes we apply all counties, which – according to the World Bank nomenclature – are classified as low-income and lower-middle-income economies. Our sample covers 46 countries (upper-middle-income and high-income economies are excluded from the study purposely), which are classified as developing economies. The time framework is set for the period of 2000-2011. All data necessary for the analysis are derived from World Telecommunication/ICT Indicators Database 2012 (16th edition).
Keywords: O11; O33; O57; 330; Information and Communication Technologies; adoption patterns; technology diffusion; S-shape curve; developing countries